Differences in IL-6 Levels Based on Clinical Severity and Outcome of COVID-19 Patients at Dr. M. Djamil Hospital - Chicy Widya Morfi; Yessy Susanty Sabri; Dessy Mizarti (Indonesian Society of Respirology (ISR), 2023)
ground: A cytokine storm is defined by elevated levels of proinflammatory cytokines such as interleukin-6 (IL-6). In COVID-19 infection, IL-6 is superior to C-reactive protein (CRP) and other inflammatory markers in predicting respiratory failure. The IL-6 is the main cytokine triggered by T cells when a cytokine storm occurs. IL-6 is the most important driver of immune dysregulation and ARDS in COVID-19 infection. The purpose of this study is to assess differences of IL-6 levels based on clinical severity and outcomes in COVID-19 patients at Dr. M. Djamil Hospital. Method: The study took place at Dr. M. Djamil Hospital from November 2021 to November 2022. This is a retrospective cohort study in which patients were tested for IL-6 levels between January 1st, 2021 and December 31, 2021. The distribution of the frequency and proportion of each variable is included in univariate analysis; bivariate analysis determines the correlation between the independent variables (clinical severity, length of stay, and final status of hospitalization) and the dependent variable (IL-6 levels in COVID-19 patients). Results: Patients' characteristics in this study, the majority of patients aged 18-49 years. Women and patients with moderate disease were more common. The majority of patients were treated for less than 14 days, and the final status of hospitalization the patients showed that most of the patients recovered. IL-6 levels with median (min-max) was 32.00 (1.50-589.00). The IL-6 levels were higher in clinically critical COVID-19 patients (77.20 mg/L), in patients with a shorter length of stay (14 days) (36.00 mg/L), and at final status of hospitalization were death (58.90 mg/L). Conclusion: There were differences of IL-6 level based on clinical severity and final hospitalization status of COVID-19 patients, but not from the length of stay in COVID-19 patients at Dr. M. Djamil Hospital.